Developing Higher Order Thinking Laboratory (Hot-Lab) to Promote General Scientific Reasoning of Student-Teachers in Physics Practices - Fathiah Alatas; Ahmad Suryadi; Firman Harris Saputra (Universitas Muhammadiyah Makassar, 2023)
This study aims to develop physics practicum guidelines that can improve students' scientific reasoning. The development of practicum guidelines in this study was based on the principles of the Higher Order Thinking Laboratory (HOT-Lab). Using the ADDIE design, which consists of five stages: analyze, design, develop, implement, and evaluate, general physics practicum guidelines are developed in three parts, namely pre-practicum, lab, and post-practicum. The participants involved consisted of two groups: five experts and 88 students taking general physics courses. The pre-practicum stage is the part that distinguishes this practicum guideline from conventional practicum guidelines, where students are presented with